The Influence of Brand Image Quality to Students Expectation and Satisfaction of Lecture at Politeknik Indonusa Surakarta - Sari, A. Anditha (Jurnal The Messenger, 2018)
An educational institution should be able to prove the quality of education. Consumers, in this case are students, need the proof of achievement, assessment, certification of quality, and the success of the alumni in getting work related to the field of knowledge. Evaluation is also needed to gain recognition from the community, as well as changes in curriculum and teaching methods that impact to better quality of the graduates. This study aims to analyze brand image influence to the expectations and satisfaction of students by taking sample 100 students from 5 study program i.e D3 Mass Communication, Hospitality, Informatics Management, Automotive, and Pharmacy by using systematic sample technique. Sample criteria that are students who have studied in semester 3 because students with the criteria should be able to evaluate their campus. The result of study indicates that brand image has significant effects to the expectation and satisfaction of the students.